Impact of Mindfulness-Based Cognitive Therapy on Depressive Symptoms Reduction among Depressed Patients in Nigeria: A Randomized Controlled Trial. (3rd July 2021) - Musa, Zulkiflu Argungu; Soh, Kim Lam; Mukhtar, Firdaus; Soh, Kwong Yan; Oladele, Tajudeen Olalekan; Soh, Kim Geok
Abstract: Depression is a common mental health disease with a high risk of relapse in people with a mental health condition. Mindfulness-based cognitive therapy (MBCT) showed higher efficacy in reducing depressive symptoms and prevent relapse for depressed patients. The study examined the effectiveness of MBCT versus the control group (CG) for the depression symptom reduction. A controlled trial was used to examine the effectiveness of MBCT or CG on depressive patients in Nigeria. Out of 357 screened subjects, 101 patients were randomized to receive either MBCT ( n = 50) or CG ( n = 51) and prospectively followed for 2 months. The intervention delivered according to the published manuals, and Beck Depression Inventory (BDI) was used to assess MDD severity among the patients. All assessments were conducted at three levels (baseline, 2 and 4 months). At the end of the 8 weeks of MBCT intervention, MBCT participants did not have significantly fewer depressive symptoms compared to those in the CG. However, the MBCT group had a significant depressive symptom reduction after 2 month follow up. The findings are in line with other studies, which show MBCT significantly decreased depression severity and improved treatment response rates after 2 months follow up, confirmed MBCT viability in the management of MDD.